2022
DOI: 10.3390/biology11071054
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Stress and Characteristics of Cold-Induced Vasodilation in Women and Men during Cold-Water Immersion: A Randomized Control Study

Abstract: Background: Cold-induced vasodilation (CIVD) is a phenomenon that refers to a paradoxical increase in finger temperature that sometimes occurs during cold exposure. The aim of this study was to compare CIVD responses between women and men, during exposure to different environmental conditions. Methods: Seven men and seven women participated in a matched controlled study consisting of a familiarization protocol followed by three experimental sessions (cool (10.8 °C WBGT), thermoneutral (17.2 °C WBGT), and hot (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Regarding to heat conserving mechanisms, some authors have described that women display a greater activity of the SNS innervating cutaneous vessels and a greater skin vasoconstriction in response to cold, especially in the luteal phase ( 84 86 ), while others found a lower SNS activity and a lower ( 87 ) or similar ( 88 ) cold-induced vasoconstriction in comparison to men. Furthermore, a similar cold-induced vasodilation (CIVD) was observed in both sexes ( 85 , 89 ), or, conversely, a higher frequency of CIVD events was detected in women ( 90 ).…”
Section: Sex Differences In Thermosensation and Thermoregulationmentioning
confidence: 78%
“…Regarding to heat conserving mechanisms, some authors have described that women display a greater activity of the SNS innervating cutaneous vessels and a greater skin vasoconstriction in response to cold, especially in the luteal phase ( 84 86 ), while others found a lower SNS activity and a lower ( 87 ) or similar ( 88 ) cold-induced vasoconstriction in comparison to men. Furthermore, a similar cold-induced vasodilation (CIVD) was observed in both sexes ( 85 , 89 ), or, conversely, a higher frequency of CIVD events was detected in women ( 90 ).…”
Section: Sex Differences In Thermosensation and Thermoregulationmentioning
confidence: 78%
“…The increased prevalence in women was a consistent finding in the studies analyzed in this review, and one of our eligible studies suggested that the higher prevalence of chilblains in women may be due to behavioral reasons, such as the choice of clothing [ 37 ]. While there are distinct differences in behavioural thermoregulation patterns between sexes [ 38 ], to date, no studies have been examined the impact of sex on the physiology of chilblains, yet a recent randomized control study on the impact of cold exposure on vasomotion reported that women show increased skin blood flow in the fingers, compared to men, when exposed to a potent cold stress [ 39 ]. This increased skin blood flow should protect women from cold injury, which is contrary to the present findings of higher prevalence of chilblains in women.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Participants started the hand immersion procedure by placing their right hand in warm (35 °C) water for 5 min to standardize hand temperature prior to the start of cold-water immersion (Tsoutsoubi et al 2022 ; Tyler et al 2015 ). Immediately after hand immersion in warm water, participants placed their hand into cold water (to the level of the ulnar styloid process) to begin the first cold immersion.…”
Section: Methodsmentioning
confidence: 99%
“…Strong CIVD responses may help maintain dexterity and tissue temperature of the fingers and toes during cold exposure, and may also delay the onset, or prevent the occurrence, of frostbite (Wilson and Goldman 1970 ; Daanen and Van der Struijs 2005 ). CIVD is often assessed by measuring finger skin temperature or skin blood flow during a 30-min hand immersion in cold water and is characterized by several components: (1) vasodilation onset time (Δt onset ), (2) mean finger skin temperature (T mean ), (3) minimum finger skin temperature (T min ), (4) magnitude of response (increase in finger temperature), and (5) frequency of response (how often vasodilation occurs); (Daanen 2003 ; Daanen and van der Struijs 2005 ; O’Brien 2005 ; Tsoutsoubi et al 2022 ). These CIVD elements play important roles in how well hand and foot temperatures are maintained and recover in cold environments.…”
Section: Introductionmentioning
confidence: 99%